Protein O-Fucosyltransferase 2 Is Not Essential for Plasmodium berghei Development - Sanz, Silvia; Aquilini, Eleonora; Tweedell, Rebecca E.; Verma, Garima; Hamerly, Timothy; Hritzo, Bernadette; Tripathi, Abhai; Machado, Marta; Churcher, Thomas S.; Rodrigues, João A.; Izquierdo, Luis; Dinglasan, Rhoel R. (Frontiers in Cellular and Infection Microbiology, 2019)
Thrombospondin type I repeat (TSR) domains are commonly O-fucosylated by protein O-fucosyltransferase 2 (PoFUT2), and this modification is required for optimal folding and secretion of TSR-containing proteins. The human malaria parasite Plasmodium falciparum expresses proteins containing TSR domains, such as the thrombospondin-related anonymous protein (TRAP) and circumsporozoite surface protein (CSP), which are O-fucosylated. TRAP and CSP are present on the surface of sporozoites and play essential roles in mosquito and human host invasion processes during the transmission stages. Here, we have generated PoFUT2 null-mutant human and rodent malaria parasites and, by phenotyping them throughout their complete life cycle, we show that PoFUT2 disruption does not affect the growth through the mosquito stages. This unexpected result indicates that the O-fucosylation of TSR domains is not essential for parasitic development under laboratory conditions.